Pemberdayaan Remaja pada Pencegahan Dini Penyakit Menular Seksual (PMS) pada Remaja di Desa Bangun Rejo Tahun 2025 - Srininta Srininta; Mesrida Simarmata; Kamelia Sinaga; Siti Nuraisyah; Febri Dyah; Cindi Desi Puspa Lumban Gaol (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Background: Sexually transmitted diseases (STDs) are infectious diseases transmitted through sexual contact including vaginal, anal, oral intercourse and are caused by bacteria, viruses, and parasites, either directly or indirectly. Half of the 15-24 year olds contribute to sexually transmitted infections in the world. Objective: so that adolescents in Bangun Rejo Village are able to independently maintain their reproductive health to avoid sexually transmitted diseases. Method: Providing education about the prevention of sexually transmitted diseases in adolescents. The number of adolescents is 30 people. Population: all adolescents in Hamlet II, Bangun Rejo Village. Sample: all populations or total sampling. Data is frequency distribution. Results: before education, adolescents' knowledge about the prevention of infectious diseases was mostly lacking as many as 12 people (40%) and a minority of good as many as 7 people (23.3%), while after education, the results obtained were a majority of good as many as 16 people (53.3%) and a minority of less as many as 5 people (16.7%). Conclusion; There was an increase in knowledge after education about early disease prevention about sexually transmitted diseases in adolescents in Bangun Rejo Village. Suggestion: Provide counseling facilities for adolescents regarding sexually transmitted infections.